Asuhan Keperawatan Pada Ny.S Dengan Osteoartritis (OA) Genu Grade III Post Total Knee Replacement Sinistra di Rumah Sakit Umum Pusat Haji Adam Malik Medan - Dudut Tanjung; Diyan Marsella Sirait; Edianto Edianto; Dina Afriani; Saodah Hanim (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Background: Osteoarthritis (OA) is a degenerative disease that often causes pain, disability and limited mobility, especially in the elderly. Total Knee Replacement (TKR) is one of the preferred surgical interventions in severe OA to reduce pain and improve joint function. Objective: This case report aims to evaluate nursing care in a 76-year-old female patient with OA genu grade III postoperative TKR sinistra accompanied by acute pain, impaired physical mobility, and risk of infection. Methods: This study is a case report using interview techniques, observation, physical examination, and documentation study. Nursing management was carried out based on the Indonesian Nursing Diagnosis Standards (SDKI), Indonesian Nursing Outcome Standards (SLKI), and Indonesian Nursing Intervention Standards (SIKI). Prioritized nursing diagnoses include acute pain, impaired physical mobility, and risk of infection. Results: After 3x24 hours of intervention, there was a decrease in the patient's pain scale from 5 to 3 (0-10 scale). Left lower limb muscle strength increased, with active range of motion. The surgical wound remained dry with no sign of infection, and the patient was able to sit on the edge of the bed with minimal assistance. Conclusion: The application of nursing care based on SDKI, SLKI, and SIKI showed significant results in improving the patient's condition. The Evidence-Based Nursing (EBN) approach contributed greatly to the recovery of patients after TKR surgery. This intervention can be a reference for nurses in designing nursing care in similar cases.